Cyclo[(6-amino-6-deoxy-D-galactonic acid)(4)]: a new class of carbopeptoid-cyclodextrin - Mayes, B; Stetz, R; Ansell, C; Fleet, G (2004)
The formation of the 28-membered ring cyclo[(6-amino-6-deoxy-D-galactonic acid)4] by cyclisation of a protected open chain fully hydroxylated nylon 6 linear tetramer in modest yield provides the first example of a new class of carbopeptoid-cyclodextrin. © 2003 Elsevier Ltd. All rights reserved.